Same Difference? Low and High Glucosinolate Brassica rapa Varieties Show Similar Responses Upon Feeding by Two Specialist Root Herbivores - Sontowski, Rebekka; Gorringe, Nicola J.; Pencs, Stefanie; Schedl, Andreas; Touw, Axel J.; van Dam, Nicole M. (Frontiers in Plant Science, 2019)
Glucosinolates (GSLs) evolved in Brassicaceae as chemical defenses against herbivores. The GSL content in plants is affected by both abiotic and biotic factors, but also depends on the genetic background of the plant. Since the bitter taste of GSLs can be unfavorable for both livestock and human consumption, several plant varieties with low GSL seed or leaf content have been bred. Due to their lower GSL levels, such varieties can be more susceptible to herbivore pests. However, low GSL varieties may quickly increase GSL levels upon herbivore feeding by activating GSL biosynthesis, hydrolysis, or transporter genes. To analyze differences in herbivore-induced GSL responses in relation to constitutive GSL levels, we selected four Brassica rapa varieties, containing either low or high root GSL levels. Plants were infested either with Delia radicum or Delia floralis larvae. The larvae of both root flies are specialists on Brassica plants. Root samples were collected after 3, 5, and 7 days. We compared the effect of root herbivore damage on the expression of GSL biosynthesis (CYP79A1, CYP83B2), transporter (GTR1A2, GTR2A2), and GSL hydrolysis genes (PEN2, TGG2) in roots of low and high GSL varieties in conjugation with their GSL levels. We found that roots of high GSL varieties contained higher levels of aliphatic, indole, and benzyl GSLs than low GSL varieties. Infestation with D. radicum larvae led to upregulation of indole GSL synthesis genes in low and high GSL varieties. High GSL varieties showed no or later responses than low varieties to D. floralis herbivory. Low GSL varieties additionally upregulated the GSL transporter gene expression. Low GSL varieties did not show a stronger herbivore-induced response than high GSL varieties, which indicates that there is no trade-off between constitutive and induced GSLs.